X-ray Radiographic Study of Simulated Voids –like Defects in Al -Castings and Welded Joints in Steel - Mahrok, Mazin; Juma, Thamir; Saeed, Farqad (Al-Nahrain Journal of Science, 2013)
The detection and evaluation of imperfections in internal structures of castings and welded joints by x-ray radiography were studied. Optimum radiography conditions that improved the radiographic detection were attempted.Mathematical equations for radiography were used to calculate the size and depth of defects in castings were tested for validity to a wide range of parameters commonly used in radiography and for variable density and shape of the defects with respect to surrounding.Two kinds of samples are prepared. The first is aluminum casting through which two different sizes of a regular steel spheres are included and then radiographed from two opposite sides to estimate their dimensional information from the radiographs. The second sample is steel plates which are welded and then radiographed by x-rays. Imperfections such as incomplete root penetration, undercut and porosity were detected in the radiographs.